Adherence to the Mediterranean diet and consumption of functional foods among the Balearic Islands' adolescent population. Issue 4 (8th May 2014) - Ozen, Asli Emine; Bibiloni, Maria del Mar; Murcia, María Antonia; Pons, Antoni; Tur, Josep A
Abstract Objective To assess differences in adherence to the Mediterranean diet (MD) between consumers and non-consumers of functional foods among the Balearic Islands' adolescent population. Design Cross-sectional nutritional survey carried out (2007–2008) in the Balearic Islands, a Mediterranean region. Dietary assessment was based on a semi-quantitative FFQ and two non-consecutive 24 h recalls. Anthropometric measurements and questions related to socio-economic status, physical activity and adherence to the MD were assessed. Setting Data obtained from a representative sample of all inhabitants living in the Balearic Islands aged 12–17 years. Subjects A random sample (n 1961) of the adolescent population was interviewed. Results The mean adherence to the MD among consumers of functional foods was 56·42 (sd 6·05) % and 55·76 (sd 5·41) % among non-consumers. Consumption of fruit juice, fibre-rich bread/cookies, cereal bars, fish and soya milk was higher among adolescents with high MD adherence, and consumption of modified milk, probiotics, breakfast cereals and infusions was higher among adolescents with low MD adherence. Daily intakes of functional dietary components from plant foods (dietary fibre, vitamins C and E, carotene, folic acid) were higher among adolescents with high MD adherence. Conclusions The Balearic Islands' adolescent population had moderate adherence to the MD; higher adherence was observed among consumers of functional foods. Average daily intakes of functional foods and functional dietary components were higher among adolescents with high adherence to the MD. Gender, age and low parental education were risk factors for low adherence to the MD, mainly among non-consumers of functional foods.